2006
DOI: 10.1055/s-2006-932503
|View full text |Cite
|
Sign up to set email alerts
|

Free Anterolateral Thigh Flap for Reconstruction of Major Craniofacial Defects

Abstract: Free-tissue transfer has revolutionized skull-base surgery by expanding the ability to perform cranial base resection and by improving the quality of reconstruction. The anterolateral thigh flap has come recently into use in the field of head and neck reconstruction. Its role in craniofacial and midface reconstruction has not been specifically defined. This study involved a total of 18 patients who were treated over a 5-year period from 1998 to 2003. Seventeen patients had locally advanced head and neck cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 28 publications
(39 reference statements)
1
34
0
2
Order By: Relevance
“…T he anterolateral thigh (ALT) flap, first described as a septocutaneous perforator-based flap by Song et al (1) in 1984, has recently gained popularity and has become an important option for reconstruction of multiple anatomical locations such as the head and neck (3)(4)(5)(6)(7)9,10,(12)(13)(14)16,(18)(19)(20)(21)(22)(23)(25)(26)(27)(28)(29)(30)32,34,36,38,39,(41)(42)(43), upper (15)(16)(17)(18)(19)26,32,35,37,38,42) and lower (8,(16)(17)(18)(19)22,24,…”
mentioning
confidence: 99%
“…T he anterolateral thigh (ALT) flap, first described as a septocutaneous perforator-based flap by Song et al (1) in 1984, has recently gained popularity and has become an important option for reconstruction of multiple anatomical locations such as the head and neck (3)(4)(5)(6)(7)9,10,(12)(13)(14)16,(18)(19)(20)(21)(22)(23)(25)(26)(27)(28)(29)(30)32,34,36,38,39,(41)(42)(43), upper (15)(16)(17)(18)(19)26,32,35,37,38,42) and lower (8,(16)(17)(18)(19)22,24,…”
mentioning
confidence: 99%
“…The use of ALT flap has been widely described in literature and today is worldwide considered as the first choice for several kind of defects reconstruction: RodriguezVegas et al 17 reported its use without bone grafts in reconstruction of complex orbitomaxillary defects supporting the flap reliability for such reconstructions; Agostini et al, 18 Valentini et al, 19 and Chen et al 20 confirmed the ALT application in oral cavity reconstruction, underlining the versatility of the flap for the restoration of the internal oral lining. Other authors, such as Malata et al 21 and Amin et al, 22 reported their experience with ALT flap for skull base and craniofacial defects reconstruction, focusing on the large amount of well revascularized tissue provided used for the filling of the death spaces, the low rate of complications and the stability of the results obtained. Finally, Mureau et al 23 and Hong et al 24 presented their experience with the use of ALT flap for the external coverage reconstruction, with particular care to the donor site morbidity and the final cosmetic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…If critical segments of bone are missing, such as the orbital rim or the anterior floor of the orbit, nonvascularized bone grafts can provide the needed support. Other flap options, depending on the amount of soft-tissue bulk required, include the lateral arm flap, anterolateral thigh flap, [57] and scapula flap.…”
Section: Treatmentmentioning
confidence: 99%